2020
DOI: 10.4314/njp.v47i3.14
|View full text |Cite
|
Sign up to set email alerts
|

Thanatophoric dysplasia type 1 as seen in a tertiary institution in South-East Nigeria: A case report

Abstract: Thanatophoric dysplasia is a lethal form of skeletal dysplasia seen in neonates. The word ‘thanatophoric’ is derived from the Greek word  thanatophorus meaning death bringing. Thanatophoric dysplasia results from mutations within the Fibroblast Growth Factor Receptor 3 (FGFR3) gene which is located on chromosome 4p16.3. A female neonate with dysmorphic features such as macrocephaly, frontal bossing, periorbital  swelling and depressed nasal bridge was delivered to a 35year old woman. The upper and lower limbs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…This highlights the difficulty that may be associated with antenatal diagnosis. Several authors have, on the contrary, reported cases of TD correctly diagnosed in-utero with sonographic examination [ 11 , 12 ]. Skeletal dysplasias can be diagnosed in-utero with increasing accuracy as the pregnancy advances.…”
Section: Discussionmentioning
confidence: 99%
“…This highlights the difficulty that may be associated with antenatal diagnosis. Several authors have, on the contrary, reported cases of TD correctly diagnosed in-utero with sonographic examination [ 11 , 12 ]. Skeletal dysplasias can be diagnosed in-utero with increasing accuracy as the pregnancy advances.…”
Section: Discussionmentioning
confidence: 99%
“…Type II TD is characterized by micromelia with straight femurs and the uniform presence of moderate and severe craniosynostosis with cloverleaf-like skull deformation due to premature closure of the coronal and lambda-like sutures [4,7,13,17,18,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The differential diagnosis of TD should include imperfect osteogenesis type II, characterized by fractures of long bones, and achondrogenesis, characterized by extreme hypomineralization but without the classic multiple skin folds [8,18,29]. The differential diagnosis also includes Ellis-Van Creveld syndrome (chondroectodermal dysplasia), asphyxial thoracic dysplasia, chondrodysplasia syndrome with polydactyly, severe hypophosphatasia, and homozygous achondroplasia [19,31].…”
Section: Introductionmentioning
confidence: 99%
“…3 There are no prevalence reports from Nigeria probably because of nonreporting however there have been few case reports by Joel-Medewase et al, Komolafe et al and Daniyan et al in South-West and South-Eastern Nigeria respectively. [4][5][6] These infants are born with severe shortening of lower limbs, and underdeveloped lungs resulting in respiratory difficulty at birth or shortly after. Some cases have been reported to have died in utero while others died a few ABSTRACT Thanatophoric dysplasia is a rare congenital severe skeletal disorder previously considered lethal but some survivals beyond the neonatal period have been reported due to extensive medical interventions.…”
Section: Introductionmentioning
confidence: 99%